The Potential for Web Services to Enhance Information Access to Legacy Data: An Exploratory Study and Application - Oguz, Fatih; Moen, William E. (University of North Texas, 2006)
This paper presents an overview of an exploratory research project to identify, describe, and investigate the applicability of the Web services (WS) approach to access legacy data. In the Z Texas Implementation Component of the Library of Texas (ZLOT) project, the ZLOT technical team has implemented a multi-purpose Texas Library Directory Database (TLDD) that is used as a back-end database to support the Library of Texas (LOT) Resource Discovery Service (RDS). The researchers developed and implemented a prototype WS application to show how a legacy system can be accessed and its data can be searched and retrieved. This study focused on understanding how requests and responses between software applications are encoded in Extensible Markup Language (XML).
Keywords: Web services; SRU/W; Information storage and retrieval systems; Information technology